Environment, crops and harvesting strategies during the II millennium BC: Resilience and adaptation in socio-economic systems of Bronze Age communities in Apulia (SE Italy). (2nd May 2017) - Primavera, M.; D'Oronzo, C.; Muntoni, I.M.; Radina, F.; Fiorentino, G.
Abstract: The socio-cultural dynamics of the Bronze Age communities of Apulia (S-E Italy) during the 2nd millennium BC represent a crucial moment in the history of the relationship between humans and nature. Over the last few decades, several studies have highlighted the complex pattern of Late Holocene climate shifts across the Mediterranean region and the difficulties in distinguishing these changes from human impacts in many proxy records. This study consists of a regional-diachronic overview of Bronze Age archaeobotanical data, pertaining to south-eastern Italy, derived from charcoal and seed/fruit analysis performed on materials from several archaeological sites distributed across Apulia. The aim is to identify possible plant-related changes in subsistence strategies during a period of transformation in the environment as well as cultural systems. It follows an integrated approach in which the shifts in plant assemblages (seeds/fruits and charcoals) are considered in the light of high-resolution palaeoclimate proxies, available for the central Mediterranean area, and socio-cultural dynamics inferred from archaeological evidences. The different lines of evidence explored provide the basis for a discussion of the possible reasons for changes in subsistence strategies during the course of the Bronze Age in the area. What emerges from our analysis are major transformations of annual crop husbandry, seasonal harvesting strategies and storage technologies, one in the Middle and one in the Late Bronze Age. Although the first transformation appears to be linked to climate forces, the latter seems to be the result of social and political "pressure".